PENINGKATAN KEMAMPUAN MENULIS PERMULAAN MENGGUNAKAN MEDIA GAMBAR DAN PENDEKATAN KETERAMPILAN PROSES SISWA - sri utami (Jurnal Muara Pendidikan, 2020)
Preliminary writing is a stage of the writing process for early grade elementary school students. Students learn to acquire abilities and master techniques in writing correctly. Therefore, teachers need to design well-written learning.This research was carried out with the aim of improving the initial writing ability using image media and the process skills approach of grade 1 students at SDN 45/1 Sridadi Batanghari Regency and to find out the effectiveness of the learning process. This classroom action research uses a modified Kemmis and Mc Taggart model that uses a spiral self-reflection system that begins with planning, action, observing, reflecting, re-planning as the basis for a problem solving approach. Based on the results of the research that has been done, it can be concluded that the use of image media with a process skill approach can improve the initial writing ability of grade 1 elementary school students in writing stories simply stories.